Burden of Silicosis among stone crushing workers in India. (3rd November 2021) - Govindagoudar, M B; Singh, P K; Chaudhry, D; Chaudhary, R; Sachdeva, A; Dhankhar, S; Tyagi, D
Abstract: Background: In North India, the mining industry is disorganized and profit-driven. It predisposes its workers towards the development of silicosis. Haryana, a major North Indian state, has developed a compensation–rehabilitation policy for mining workers. Aims: This study is the review of the policy's functioning and limitation from the first 4 years of implementation. Methods: The labour department does surveillance of workers in the mining industry. All suspected cases of silicosis are evaluated by a multidisciplinary team. Based on the final diagnosis, the compensation is decided. Results: Nearly 5000 workers were screened, and 729 appeared before the medical board. Of these 729, 465 were having silicosis, and their data are presented here (data of 7 patients were missing). All workers were males. The mean age was 44.54 ± 9.6 years, and the mean exposure (work experience) was 17.25 ± 6.7 years. Most of the workers were between the age of 40 and 50 years and had exposure for 10–20 years. Chest radiography examination showed that progressive massive fibrosis (large size type C opacities) was the most common type of presentation (23%). Smaller opacities (p, q, r and s, t, u) were combined for further analysis, given their similar prognostic significance. It was found that age and experience both had a linear and significant correlation with the severity of lung involvement. Conclusions: Nearly a quarter of subjects were suffering from the worst type of lung involvement at screening itself. The policy has laid a foundation for the welfare of workers, but there is still a long way to go.